Accessory mineralisations in lherzolites of Northern Kraka massif (South Urals) - D. E. Saveliev; R. A. Gataullin (Georesursy)
The findings of platinum group metal mineralization (PGM) and the distribution of platinum group elements (PGE) in lherzolites of the Northern Kraka massif are described. The total contents of PGE are approximately two orders of magnitude lower than those in chondrite and are close to pyrolite, relative to which the studied lherzolites are enriched in Pd and depleted in Ru. In segregations of PGMs, the presence of all PGEs (except rhodium) in various proportions was established. All found grains are divided into three contrasting types: the refractory triad Os–Ir–Ru, essentially platinum with the participation of Pd, and Cu–Pd. Almost all found PGM grains are localized either in the peripheral parts of grains of altered sulfides (heazlewoodite, pentlandite) or in the silicate matrix in the immediate vicinity of sulfide segregations. Based on the mineral associations and PGE distribution, a probable genesis of segregations has been suggested. Associations of Cu–Pd and Pd–Pt(+Cu) composition most likely formed during the crystallization of sulfides from the extracted partial melts. This is indicated by their close association with clinopyroxenes and the presence of relatively fusible platinoids and copper. The associations of Pt–Ir and Os–Ir–Ru(+Pt) composition are most likely restitic, formed in place of primary mantle sulfides as a result of extraction of more fusible elements and further desulphurization. The isolation of platinoids as their own mineral phases is associated with the influence of superimposed low-temperature processes – subsolidus redistribution during cooling and subsequent serpentinization.